Kebolehan Penaakulan Induktif Di Kalangan Pelajar Berumur 12 Tahun Di Sebuah Sekolah Rendah - Phillips, John Arul (Penerbit Universiti Sains Malaysia, 1993)
Inductive reasoning requires an individual to reason from part to whole or from particular to general. It involves reasoning based on given premises wherein the conclusion arrived at is certain. This study attempts to determine the reliability of a 48-item Inductive Reasoning Test (IRT) developed by the researcher and to examine its relationship to academic achievement, socio-economic status and gender